Community engagement in genomic research: Proposing a strategic model for effective participation of indigenous communities. Issue 4 (10th August 2021) - Ogunrin, Olubunmi; Gabbay, Mark; Woolfall, Kerry; Frith, Lucy
Abstract: Community engagement (CE) contributes to successful research. There is, however, a lack of literature on the effectiveness of different models of CE and, specifically, on CE strategies for the conduct of genomic research in sub‐Saharan Africa. There is also a need for models of CE that transcend the recruitment stage of engaging prospective individuals and communities and embed CE throughout the research process and after the research has concluded. The qualitative study reported here was designed to address these knowledge gaps and comprised of 36 key informant semi‐structured interviews and fifteen focus groups with 50 participants. We interviewed selected stakeholders in genomic research in Nigeria: biomedical researchers, community rulers, opinion leaders, community health workers, and prospective research participants. We explored these stakeholders' views on their understanding of community engagement, their expectations, experiences, and their opinions on acceptable processes of community consultation in genomic research. The methodological design, adapted from grounded theory, used the constant comparative method of data analysis; while normative conclusions were made using the symbiotic empirical ethics approach. Data analysis revealed five main themes important for successfully engaging communities in genomic research: effective communication, diversity of community gatekeeping, trust, cultural integration of research, and conservation of the research setting. From these themes, we have developed a four‐stage model of community engagement that covers all stages of the research process; namely, the Community Approach, Intermediate phase, Collaboration and Post‐research Cordiality model (CICP). This model could be used to improve the integration of CE in genomic research among local communities.